Lactancia materna exclusiva. Lo que no se les dice a las madres. (2024)
The support and accompaniment of both the family and society are essential so that mothers can guarantee an adequate practice of exclusive breastfeeding. Breastfeeding is influenced by different situations such as level of education, maternal health, culture, among others. In this document, a reflection is made on how the support is being carried out and what the breastfeeding education that pregnant and lactating women currently receive is currently. The education that nursing mothers receive from health institutions, health professionals, nutritionists, doctors, pediatricians, nurses, nursing assistants is not adequate, nor is it timely since the author considers that it is not being given. the importance of adequate nutrition for boys and girls under 6 months.